1989
DOI: 10.2307/1130779
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' and Parents' Reasoning about Actual Family Conflict

Abstract: This study employed a distinct domain perspective on social-cognitive development to assess reasoning about issues of family conflict. Subjects were 102 fifth through twelfth graders from 2-parent families and their parents. Individually interviewed family members described actual family conflicts and, for each, justified their position on the dispute and reasoned about them from the other's perspective. Parents generated fewer conflicts than did children. Preadolescent to late adolescent families generally ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
385
7
39

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(481 citation statements)
references
References 0 publications
50
385
7
39
Order By: Relevance
“…Conflict in parent-adolescent relationships has been found to be higher for girls than for boys (Laursen 1995) and more conflicts occurred with mothers than with fathers (Laursen 1995;Smetana 1989). These gender differences can possibly be explained by the earlier pubertal development of girls, since parent-adolescent conflicts of earlier maturing adolescents are higher regarding both frequency and intensity (Collins and Laursen 2004).…”
Section: Development Of Support Conflict and Powermentioning
confidence: 99%
See 2 more Smart Citations
“…Conflict in parent-adolescent relationships has been found to be higher for girls than for boys (Laursen 1995) and more conflicts occurred with mothers than with fathers (Laursen 1995;Smetana 1989). These gender differences can possibly be explained by the earlier pubertal development of girls, since parent-adolescent conflicts of earlier maturing adolescents are higher regarding both frequency and intensity (Collins and Laursen 2004).…”
Section: Development Of Support Conflict and Powermentioning
confidence: 99%
“…These gender differences can possibly be explained by the earlier pubertal development of girls, since parent-adolescent conflicts of earlier maturing adolescents are higher regarding both frequency and intensity (Collins and Laursen 2004). Also, both daughters and mothers are less avoidant regarding conflict (Laursen 1995) and conflicts are mainly on everyday issues (Smetana 1989) in which mothers are more involved (Collins and Laursen 2004;Laursen 1995). Furman and Buhrmester (1992) did not find gender differences for boys and girls or for mothers and fathers regarding conflict, but reported that boys felt more powerful in relationships with their parents compared to girls and late adolescents felt more powerful in relationships with their mothers compared to relationships with their fathers.…”
Section: Development Of Support Conflict and Powermentioning
confidence: 99%
See 1 more Smart Citation
“…Studies often have revealed opposite conclusions, as well as complicated interactions between parents ' and adolescents ' gender, as suggested above. Studies have indicated, for example, that mother -daughter relationships become particularly disrupted and conflictual during adolescence (Buchanan et al, 1990 ;Holmbeck & Hill, 1991 ;Montemayor, 1982Montemayor, , 1986Smetana, 1988aSmetana, , 1989Smetana, Daddis, & Chuang, 2003 ), although other research has not supported this pattern (Hill & Holmbeck, 1986 ;Smetana, Yau, & Hanson, 1991 ;Papini et al, 1988 evidence that adolescent girls perceive higher levels of autonomy support from parents, and are granted more input into family decision making (Beyers & Goossens, 1999 ;Brown & Mann, 1990 ;Flanagan, 1990 ;Fuligni & Eccles, 1993 ;Holmbeck & O ' Donnell, 1991 ;Jacobs, Bennett, & Flanagan, 1993;Soenens et al, 2007 ). However, these differences may at least partially depend on the gender of the parent and on other family characteristics, such as cultural context and parental attitudes toward gender roles (Bumpus, Crouter, & McHale, 1998 ;Daddis & Smetana, 2005 ).…”
Section: Attachment Autonomy and Gendermentioning
confidence: 99%
“…Interviewing parents and their adolescent children about family norms and rules, Smetana (1988) found that mothers were seen by their spouses and by their children as being in charge of enforcing family norms concerning physical appearance. Spitzack (1990) described that both parents exerted considerable influence on their children's physical appearance and eating, and that parents differed in how they influenced their children, whereby "mother criticizes, father compliments" (p. 83).…”
mentioning
confidence: 99%